On scripting GRASS GIS: Building location-independent command line tools - Peter Loewe (Geoinformatics FCE CTU, 2010)
This paper discusses scripting techniques within the context of GRASS GIS. After an overview over scripting for interactive GRASS sessions, it is shown how GRASS GIS-provided functionality can be used for external applications. This approach of external scripting allows for the application of GRASS GIS-based functionality to be used for standalone applications and embedding in larger automated workflows.